Analysis of Fibronectin and TGF-β1 Immunoexpression to Determination of Wound Vitality in Wistar Rats (Rattus norvegicus) - Nita Novita; Hasrayati Agustina; Bethy S. Hernowo; Abdul H. Hassan (Journal of Medicine and Health, 2015)
Wound examination is indispensable in forensic practice. The scientific field of wound age determination has advanced progressively during recent years.The purpose of this study was to determine the differences of fibronectin and TGF-β1 expression in both antemortem and postmortem wounds. This study was an experimental with completely randomized design.  The skin wounds (vital and postmortem) were taken from fourty Wistar rats and divided into 10 groups of rats. Immunohistochemical staining was performed to determine the differences between antemortem and postmortem wounds. The result showed that in 30 minutes after antemortem wound infliction, all of samples showed weak reactivity for fibronectin and TGF-β1 (100%).  In first hour after wound infliction, 3 samples (75%) showed weakly positive and 1 sample (25%) strongly positive for fibronectin and TGF-β1.  In 2 hour after wound infliction, 1 sample (25%) showed weakly positive and 3 sample (75%) strongly positive for fibronectin and TGF-β1.  In 3 and 4 hour after wound infliction, all of samples strongly positive for fibronectin and TGF-β1.  In postmortem wound, all of samples showed negativity for fibronectin and TGF-β1. In conclusion, fibronectin and TGF-β1 may be useful in the determination of wound vitality. Keywords: wound, fibronectin, TGF-β1, vitality